2017
DOI: 10.3390/ijms18020335
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Evaluating a Flexible Wireless Microcoil Array Based Integrated Interface for Epidural Cortical Stimulation

Abstract: Stroke leads to serious long-term disability. Electrical epidural cortical stimulation has made significant improvements in stroke rehabilitation therapy. We developed a preliminary wireless implantable passive interface, which consists of a stimulating surface electrode, receiving coil, and single flexible passive demodulated circuit printed by flexible printed circuit (FPC) technique and output pulse voltage stimulus by inductively coupling an external circuit. The wireless implantable board was implanted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Type I ACFs are conducting along the thickness direction of the membrane and insulated along the membrane surface. 5 This type of ACF has applications in smart card 6 and electronic fields. 7 On the basis of type I ACFs, type II ACFs are further developed and have different conductance along the two perpendicular directions of their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Type I ACFs are conducting along the thickness direction of the membrane and insulated along the membrane surface. 5 This type of ACF has applications in smart card 6 and electronic fields. 7 On the basis of type I ACFs, type II ACFs are further developed and have different conductance along the two perpendicular directions of their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical work in rodents has shown battery-free cortical stimulation 2729 but the stimulation amplitudes are too small to stimulate the human brain through the dura. The only large animal, battery-free epidural cortical stimulator the authors are aware of was reported in a feline model, but the translational misalignment of only ∼3 mm makes it difficult to achieve proper alignment in our use cases in the operating room (OR) or at home 30 .…”
mentioning
confidence: 99%